Pengaruh Kosa Kata Selumbari dan Tulat terhadap Upaya Pembinaan dan Pengembangan Bahasa Indonesia (Lembaga Pengembangan Kinerja Dosen, 2026)
This study investigates the influence of the vocabulary terms “selumbari” and “tulat” on efforts to develop and cultivate the Indonesian language, particularly through expanding public lexical awareness via social media. These two terms, originating from local linguistic traditions, possess significant potential to be integrated into modern Indonesian as part of cultural preservation and the strengthening of national linguistic identity. The research employed a descriptive quantitative method, collecting data through the dissemination of educational videos and Google Form questionnaires on social media platforms such as Instagram, WhatsApp, and TikTok. Respondents consisted of students, university students, the general public, and various other social groups. Analysis of responses from 20 participants revealed that most respondents had never heard or read the words “selumbari” and “tulat.” However, the majority stated that both words were easy to understand and contributed positively to vocabulary development in Indonesian. The findings indicate that social media plays a strategic role in introducing and popularizing new vocabulary to a wide audience. This study also highlights the importance of vocabulary enrichment as part of ongoing Indonesian language development, ensuring that the language remains adaptive to contemporary changes while representing local cultural richness. The implications of this research may serve as a reference for educators, linguistic institutions, and policymakers in formulating strategies to enhance vocabulary literacy, especially among younger generations.